Systems Analysis in Health Care: Framework and Example - Ammenwerth, E.; Ehlers, F.; Eichstädter, R.; Haux, R.; Pohl, U.; Resch, F. (Methods of Information in Medicine, 2002)
Objectives: Due to the high complexity of structures and processes in health care, thorough systems analyses in health care run the risk of becoming very complex and difficult to handle. Therefore, we aimed to support systematic systems analysis in health care by developing a comprehensive framework that presents and describes potential areas of analysis.Methods: A framework for systems analysis in health care was developed and applied in a health care setting. To provide a clear structure, the framework describes the potential views and levels of systems analyses in a health care environment.Results: The framework comprises five views (roles and responsibilities, information processing and tools, communication, business processes, teams structure and cooperation) and five levels of analysis (overall organization, organizational unit, staff member, role, task). The framework was successfully applied in an analysis of the structures and processes of the Department of Child and Adolescent Psychiatry of the University Medical Center Heidelberg.Conclusions: The proposed comprehensive framework aims to structure the views and levels of systems analysis in the complex health care environment. Our first experiences support the usefulness of such a framework.
Keywords: Systems analysis; communication; coordination; patient care team; delivery of health care; process assessment